Strengthening humanitarian networks: Applying the network functions ap proach - Ramalingam, Ben; Mendizabal, Enrique; Mierop, Ed (ODI, 2008)
This note offers a simple, flexible and powerful methodology — the net work functions approach (NFA) — that can be applied to analyse and str engthen humanitarian and development networks. Based on research under taken at ODI and elsewhere, the NFA suggests there are six overlapping functions that different networks perform in varying combinations. Th rough reflection on a network’s current activities and how they relate to each of these functions, the NFA helps those facilitating, acting within or supporting networks to work towards an ‘ideal’ functional mi x. The aim is for network strategies to be honed, thinking clarified, activities sharpened and ultimately, humanitarian performance improved .